Upaya Komunitas dalam Melestarikan Budaya Silat Pukul Betawi: Studi Kasus Sanggar Ulil Albab, Poris Gaga, Tangerang - Noris, Muhamad Caesar; Wati, Lina; Rahayu, Riza Gusti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Sanggar Ulil Albab is one of the cultural communities that is currently actively carrying out various cultural activities as a form of preservation. This study aims to examine how the community's efforts in preserving the Betawi martial arts culture carried out by Sanggar Ulil Albab, and discuss the obstacles faced by Sanggar Ulil Albab. The approach used in this study is a qualitative descriptive approach with a case study method. The data in this study were obtained through interviews, observations and documentation to the leaders and members of the studio. This study uses the Functionalism theory put forward by Bronislaw Malinowski. The results show that there are still efforts to preserve the Betawi martial arts culture carried out by the studio, starting from opening cultural teachings (training), participating in existing cultural events or festivals, and socialization. These preservation efforts are carried out because they have a relevant function and can meet the needs of the community. So that the studio always tries to preserve this martial arts culture.